KAJIAN LITERATUR: ADAPTIVITAS DAN RESPONSIVITAS STRATEGI PEMASARAN RUMAH SAKIT TERHADAP PERUBAHAN KEBUTUHAN PASIEN - Nazhifa Nurul Azizah,; Nasywa Athiyah Zahra,; Amanda Nurjanah,; Adzroo Atiiqoh Nur Nabiila,; Nazwa Fadya Nur Shaumi,; Raeesah Wahlullizar,; Salsabila Firdausi,; Dwi Rani Oktapiani,; Cahya Arbitera, (Journal of Innovation Research and Knowledge, 2025)
Background: Hospital face intense competition, changes in JKN regulations, and the demands of the digital age, requiring strategic management, service innovation, and the use of technology to improve their adaptability. Through the implementation of appropriate strategies, such as strengthening resources, developing information systems, and focusing on patient experience, hospital can maintain their competitiveness, improve operational efficiency, and provide higher quality healthcare services to the community. Purpose: Examining healthcare providers adaptation strategies in response to regulatory changes and patient needs, as well as analyzing the challenges in maintaining service quality. In addition, highlighting the healthcare sector’s effort to adjust its strategies in order to remain competitive amid dynamic competition. Method: Using a literature review method by searching secondary sources from various scientific databases using a combination of keywords related to hospital marketing, digitization of healthcare services, and organizational adaptability. Selection was based on specific inclusion criteria, resulting in 11 relevant articles that were analyzed as the basis for research synthesis. Result: Hospitals need to adapt their marketing strategies through digital marketing, service quality improvement, operational efficiency, and human resource strengthening to respond to changes in patient behavior and health regulations. In addition, strategies such as telemedicine, social media utilization, implementation of the 7P marketing mix, and service responsiveness have been proven to increase satisfaction, loyalty, and competitiveness of hospitals. Conclusion: Hospitals must develop adaptive and responsive marketing strategies through digital transformation, strengthening strategic management, improving service quality and patient experience, and implementing the 7Ps of marketing mix, despite facing challenges in human resources, infrastructure, and policy, in order to increase competitiveness, satisfaction, and patient loyalty amid the dynamics of the healthcare industry.